MANAJEMEN VISUAL DISCOURSE PADA BISNIS INDUSTRI EKONOMI KREATIF UMKM DESA SUKAJADI KEC. LEMAHSUGIH KAB. MAJALENGKA - Ardiansah, Dian; Setiawan, Wahdan Budi (PT. Jurnal Center Indonesia Publisher, 2025)
The seminar titled Visual Discourse in Marketing UMKM Products held in Sukajadi Village, Lemahsugih District, aimed to enhance local entrepreneurs’ understanding of visual communication strategies in product marketing. This initiative responded to the limited use of visual elements such as packaging design, symbols, and graphic narratives that reflect local identity and influence consumer perception. Through a participatory approach, participants were introduced to the basics of visual discourse, practiced culturally rooted design techniques, and simulated digital promotional content. Monitoring was conducted through direct observation and feedback, while evaluation involved pre-tests, post-tests, and analysis of participants’ design outputs. Results showed a significant improvement in visual literacy and readiness to redesign product packaging more effectively. The seminar laid a foundation for building a creative and context-sensitive UMKM ecosystem, where visual elements serve as key tools to strengthen product identity, cultural relevance, and market competitiveness.